Respuesta :
Answer:
C. f(3)=27
Step-by-step explanation:
f(3)=-4(3-6)+15
f(3)=-4(-3)+15
f(3)=12+15
f(3)=27
Answer: C) 27
Step-by-Step Explanation:
=> f(x) = -4(x - 6) + 15
Therefore, f(3) means x = 3.
Substituting the value of ‘x’ :-
=> -4(x - 6) + 15
= -4(3 - 6) + 15
= -4 * 3 + -4 * -6 + 15 (Opening brackets)
= -12 + 24 + 15
= 12 + 15
= 27
Therefore, f(3) = 27
Step-by-Step Explanation:
=> f(x) = -4(x - 6) + 15
Therefore, f(3) means x = 3.
Substituting the value of ‘x’ :-
=> -4(x - 6) + 15
= -4(3 - 6) + 15
= -4 * 3 + -4 * -6 + 15 (Opening brackets)
= -12 + 24 + 15
= 12 + 15
= 27
Therefore, f(3) = 27